Linking Content Education sebagai Navigasi pada On Line Learning System - Eko Travada S. Putro (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
The concept of on line learning system was introduced in early 2000. The development of on-line learning systems such as e-learning, blended learning, and the Massive Online Course were driven by the development of computer technology. In designing on line learning when viewed from its development in harmony with the stages of how the learning process occurs. In conventional learning systems success in the learning process is influenced by student motivation and teaching methods on the material. Teachers will try to convey the material well, so students can find out the order of material that must be learned and understand every material given. In addition, the amount of material burden delivered by the instructor must conform to the students' abilities so that the material can be absorbed. Based on the description above, the on-line learning system must be able to accommodate these two things and be supported by advances in computer technology that facilitate online-based learning. In the latest research on the On line learning system facilitated the ability to provide instructions / guides in the form of links or links between material one with the next material or other related material. which is given. The link in this paper is called Linking Content Education (LCE). In this paper we will discuss some related research regarding links as navigation in the learning process.